ESTUDO DA CINÉTICA DE SINTERIZAÇÃO EM SISTEMAS NANOPARTICULADOS DE SnO2 - Mendes, Paulo Gedeão (2009)
Several synthesis methods exist for ceramic materials. According to the method of synthesis used to prepare oxide materials different morphologic and microstructural properties can be obtained. This work consisted of studying the Co-doped tin dioxide powders synthetized by microwave-assisted hydrothermal synthesis (MAHS) and the results were compared to powders synthesized by Pechini method. Powders synthesized by MAHS presented size of particles in the order of 5 nm while the size of particles obtained by Pechini was about five times greater. Besides the characterization of those materials in the powder form, the material was compacted and sintered. Sintering at different constant hating rates of constant heating allowed the calculation of the apparent global energy of sintering using the master sintering curve model. The material synthesized by MAHS presented a smaller apparent global energy of sintering than that obtained by Pechini route, and in the same proportion of their size differences. The results of this work lead to the conclusion that the sintering process and the saturation of dopants are strongly influenced by the particle size of starting powders.